СПОРТИВНА БЕЗПЕКА: ТЕОРЕТИЧНИЙ І КОНСТИТУЦІЙНИЙ АСПЕКТИ - Палюх, Андрій Ярославович (SUPREMANCE OF LAW, 2019)
In article is emphasized that sports safety phenomenon is in some way new in domestic and foreign science, in particular, in the theory of law, it is practically not given due attention. In our opinion, the characteristic of nature and the essence of sports safety are important to leave the fundamental categories (“security”, “National security”, “personal security”, etc.). Based on the contents of the Constitution of Ukraine, in particular, its art. 49, where the human right to health care, medical care and health insurance is enshrined, it is determined that “the state cares about the development of physical culture and sports, provides sanitary and epidemiological welfare” (Part 4 of article 49). These generalized rules are detailed and specified in the sectoral legislation of Ukraine, which aims to ensure the individual’s ability to engage in various kinds of physical activities, sporting events, competitions etc. At the same time, there are some risks and threats that are intended to oblige the State, its respective authorities to establish conditions for sports safety of athletes, trainers, arbitrators, spectators and other participants athletic relations. We suggest sports safety as a subspecies of State security, the state’s responsibility, and sporting security, as a result of human rights in the field of physical education and sports. That is, sports safety is a state of security, with a minimum level of threats legal relations in the field of physical culture and sports. It includes the safety of sports facilities and the safety of sporting events, the safety of athletes and supporters, the provision of law enforcement and respect for human rights, during the sporting event is one of the tasks of law enforcement of different levels, as the competition is local, state, regional and international level. As a result of the study, it is concluded that the need for further study of such a concept as sports safety, including inter-sectoral and international legal aspects, in order to improve legal regulation in this area.
Keywords: physical culture; sports; sports safety; security; health; athletes; danger; legislation